Host-Parasite Interactions in Individuals with Type 1 and 2 Diabetes Result in Higher Frequency of Ascaris lumbricoides and Giardia lamblia in Type 2 Diabetic Individuals - Eleuza Rodrigues Machado; Núbia Oliveira Matos; Sinione Morais Rezende; Daniela Carlos; Thauana Cristina Silva; Leônia Rodrigues; Maria Jarlene Rodrigues Almeida; Maria Regina Fernandes de Oliveira; Maria Imaculada Muniz-Junqueira; Rodrigo Gurgel-Gonçalves (Journal of Diabetes Research)
Host-parasite interactions in diabetic patients might influence diabetes complications and intestinal parasitosis. The aim was to investigate the occurrence of enteroparasites in individuals with diabetes types 1 and 2. A descriptive study was designed to estimate frequencies of parasites and to compare them in individuals with diabetes types 1 and 2 from two Health Centers and one hospital in the Federal District of Brazil. Patients were allocated to the study by convenience. Three fecal samples of 156 diabetic individuals (120 type 1 and 36 type 2) were analyzed using two parasitological methods. Enteroparasites or commensals frequency in diabetics was 64%. Diabetics infected with up to six species of intestinal parasites or commensals were found. Frequencies of Ascaris lumbricoides and Giardia lamblia were higher in individuals with type 2 diabetes. The lower frequency of A. lumbricoides found in type 1 diabetes may be related to a strong Th2 response to parasites. Autoimmune response developed in type 1 diabetic individuals characterized by the production of Th1 cytokines could explain low frequency of G. lamblia. High frequency of parasites found in type 2 diabetes emphasizes the importance of periodic parasitological examinations in these individuals.